Application of interactive evolutionary strategy in fault-tolerant system capable of online self-repairing. (2017) - Yang, Xiaoyan; Li, Yuanxiang; Tong, Yala
Evolution mechanism is widely used in triple different-structure modular redundant (D-TMR) fault tolerant system to protect different modules and realise online self-repairing. How to enhance the efficiency and diversity of the generated module by evolution strategy is among the most commonly discussed. The paper puts forward a two-stage mutation evolution strategy (TMES) based on improved virtual reconfigurable architecture platform to evolve combination logical circuit. In order to improve the scalability and increase the diversity of the generated circuit, interactive evolution strategy and heterogeneous degree evaluation are introduced, and then interactive TMES (ITMES) and improved ITMES (IITMES) are presented. The proposed schemes are tested with the evolutions of a 2-bit multiplier, a 3-bit multiplier, and a 3-bit full adder. The obtained results demonstrate that IITMES scheme has better average generation and more circuit type of generated successful individual, and has the potential to strengthen the reliability of the D-TMR system.